(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article deals with innovative technologies in the field of training and education of future specialists. One of the most promising and effective innovative technologies recognized throughout the world is the «case study» – learning with the use of specific learning situations, reflection as a method of self-knowledge and self-esteem, training technologies for teaching using the project method, developing students’ communicative skills. The results of the conducted experiments showed that education in our country needs the implementation of innovative technologies. Modern, dynamically developing socio-economic realities of society require changes in the system of vocational education in the field of strengthening its practical and personal orientation, which proves the importance of the innovative technologies described by us, that will enter the system of active professional and pedagogical activity of university teachers in our country.